2021
DOI: 10.1177/10711007211015186
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and Patient-Reported Outcomes Following Peroneus Brevis Reconstruction With Hamstring Tendon Autograft

Abstract: Background: Peroneal tendon injuries are a common cause of lateral ankle pain and instability. While the use of hamstring autograft has been proposed as a viable surgical option for peroneus brevis reconstruction, reported outcomes with this technique are limited in the literature. We present patient-reported and clinical outcomes for patients who underwent peroneus brevis reconstruction with hamstring autograft. Methods: Thirty-one patients were retrospectively identified who underwent a procedure including p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 15 publications
0
8
0
Order By: Relevance
“…6,22 A reconstruction technique with hamstring tendon autograft also showed promising results in a recent case series. 7…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…6,22 A reconstruction technique with hamstring tendon autograft also showed promising results in a recent case series. 7…”
Section: Discussionmentioning
confidence: 99%
“…Otherwise, a transfer of the peroneus brevis to the peroneus longus tendon or a graft interposition is considered to be a viable option. 7,12,13,18 No clear consensus exists regarding peroneal tendon tear treatment in cases with damaged tendon substance, when only a portion of the tendon can be preserved. A biomechanical cadaver study by Wagner et al suggested that resection of two-thirds of the tendon does not necessarily increase the risk of spontaneous tendon rupture.…”
Section: Introductionmentioning
confidence: 99%
“…This responsiveness may suggest that peroneus brevis reconstruction with hamstring autograft represents a viable surgical option for patients with peroneal tendinopathy. 9 However, such data must be interpreted cautiously: validity is limited as there was no control group and there are no current studies validating PROMIS in peroneal tendon disorders.…”
Section: Foot and Ankle Tendon Injuriesmentioning
confidence: 99%
“…However, our surgeons prefer to perform a reconstruction of the peroneal tendon using a hamstring autograft. 69…”
Section: Tendon Repair and Reconstructionmentioning
confidence: 99%